Platelet-Rich Plasma Injection in Non-Operative Treatment of Partial-Thickness Rotator Cuff Tears: A Systematic Review and Meta-Analysis - Pengfei Zhu; Zhengchao Wang; Hongmei Li; Yu Cai (Medical Journals Sweden, 2022)
Objective: Partial-thickness rotator cuff tears have a high prevalence in older people. Treatment for such tears remains controversial. Platelet-rich plasma has recently attracted attention for treating partial-thickness rotator cuff tears, due to its regenerative characteristics. However, the results of application of platelet-rich plasma in non-operative treatments are unclear. The aim of this review is to evaluate the effects on shoulder function improvement and pain relief of platelet-rich plasma injection in partial-thickness rotator cuff tears, at different follow-up times (3-6 weeks, 8-12 weeks, and more than 24 weeks after treatment) compared with placebo or corticosteroids. Design: A systematic review and meta-analysis. Methods: Several databases, including PubMed, EMBASE, and Cochrane, were searched. Eleven studies met the inclusion criteria for the meta-analysis. The quality of research was evaluated using the Cochrane risk-of-bias tool. The effectiveness of platelet-rich plasma was calculated as the difference between baseline measurements and post-injection outcomes. The standardized mean difference was used to compare different outcome scales or questionnaire measurements. Statistical analysis was performed using Stata 15.0. Results: The analysis included 11 studies, with a total of 641 patients (318 treated with platelet-rich plasma and 323 controls). Compared with placebo, platelet-rich plasma exhibited significantly better effects on shoulder function improvement and pain relief at all 3 follow-up times. Compared with other conservative treatments, platelet-rich plasma exhibited significantly better effects on shoulder function and pain relief at 8-12 weeks and at more than 24 weeks after treatment. Conclusion: This review showed positive effects on shoulder function improvement and pain relief of the use of platelet-rich plasma in treating partial-thickness rotator cuff tears, especially in relatively late stages of follow-up (more than 8 weeks) after treatment. LAY ABSTRACT Partial-thickness rotator cuff tears are common, especially in older people, and can cause shoulder pain and movement limitation. Platelet-rich plasma is a platelet concentrate made from autologous blood, which may have anti-inflammatory and healing effects. This systematic review and meta-analysis collected data from existing studies to determine the specific effects of platelet-rich plasma injection on partial-thickness rotator cuff tears. The results showed that, compared with both no treatment and other conservative treatments, platelet-rich plasma reduced pain and improved shoulder function when used to treat partial-thickness rotator cuff tears. Meanwhile, the effects were most significant at 8-12 weeks and at more than 24 weeks after treatment.